Understanding the Role of Alcohol in Metabolic Dysfunction and Male Infertility - Valentina Annamaria Genchi; Angelo Cignarelli; Andrea Sansone; Dimitri Yannas; Leonardo Dalla Valentina; Daniele Renda Livraghi; Giorgia Spaggiari; Daniele Santi (Metabolites)
Purpose: Over the past 40–50 years, demographic shifts and the obesity epidemic have coincided with significant changes in lifestyle habits, including a rise in excessive alcohol consumption. This increase in alcohol intake is a major public health concern due to its far-reaching effects on human health, particularly on metabolic processes and male reproductive function. This narrative review focuses on the role of alcohol consumption in altering metabolism and impairing testicular function, emphasizing the potential damage associated with both acute and chronic alcohol intake. Conclusion: Chronic alcohol consumption has been shown to disrupt liver function, impair lipid metabolism, and dysregulate blood glucose levels, contributing to the development of obesity, metabolic syndrome, and related systemic diseases. In terms of male reproductive health, alcohol can significantly affect testicular function by lowering testosterone levels, reducing sperm quality, and impairing overall fertility. The extent of these effects varies, depending on the frequency, duration, and intensity of alcohol use, with chronic and abusive consumption posing greater risks. The complexity of alcohol’s impact is further compounded by individual variability and the interaction with other lifestyle factors such as diet, stress, and physical activity. Despite growing concern, research on alcohol’s effects remains inconclusive, with significant discrepancies across studies regarding the definition and reporting of alcohol consumption. These inconsistencies highlight the need for more rigorous, methodologically sound research to better understand how alcohol consumption influences metabolic and reproductive health. Ultimately, a clearer understanding is essential for developing targeted public health interventions, particularly in light of rising alcohol use, demographic changes, and the ongoing obesity crisis.